A Sociedade de Geografia de Lisboa e as edições próprias de Cartografia Ultramarina Oitocentista - Aires-Barros, Luis; Grego, Helena; Matias, Cristina (Africana Studia, 2020)
In this paper are referred and studied maps and city plans elaborated and edited by the Geographical Society of Lisbon from 1881 to 1894. This activity has been carried out in liaison with the Commission of Cartography. This activity has provided the following groups of maps and plans: fifteen (15) itinerary maps edited from 1882 to 1890, five (5) maps regarding the border delimitations of some old Portuguese colonies, edited from 1882 to 1894, and eleven (11) city plans presented to the Portuguese Ministry of Marine and Overseas in 1888 and 1889. Besides, it is also referred a group of ten (10) hydrographic maps of Angola and Mozambique and also a group of three (3) generic maps.